Formulation Development and Characterization of Baclofen Floating Drug Delivery System - Saravanakumar, K. (Asian Journal of Pharmaceutics (AJP), 2022)
Background: Gastro retentive systems are retained in the stomach for a prolonged period. The objective of the present study was to formulate gastro floating tablet of Baclofen respectively. Methods: The physicochemical parameters such as hardness, weight variation, variability, in-vitro dissolution studies, and floating lag time (FLT) were performed to optimize the formulations. Results: Post compression parameters were in pharmacopieal limits. The FLT of optimized formulation was found <5 min and floated on the test media (0.1N HCL) for up to 24 h. Among Nine formulations, F4 formulation provides 99.62% drug was released at 24 h. Conclusions: The formulated floating tablets showed good buoyancy properties, thus could be a promising formulation for improving bioavailability and decreasing drug toxicity.